Produksi Rennet Mucor pusillus yang Ditumbuhkan pada Limbah Padat Tapioka (Onggok) - Choliq, Abdul (Universitas Atma Jaya Yogyakarta, 2008)
The production of rennet enzyme extracted from Mucor pusillus in â€œonggokâ€ medium the effect of incubation peptone and ammonium nitrate to enzyme production, and the effect of pH and temperature to the activities of rennet were found. The statistical method used is Completed Randomized Design with 3 replicates for each treatment, with the rennet activity in RU/ml enzyme extract. The rennet production was conducted in erlenmeyer (100 ml) that contain 17.5 g â€œdry onggokâ€ and 50 ml solution of suspension used. The effect of incubation time was detected in three incubation times (4, 7, and 10 day), while effect of peptone and ammonium nitrate to the production of the rennet enzyme was detected in 4 concentrations (0, 1, 2, and 3%) for 7 days of incubation times. The effect of pH to the activity of rennet from the treatment of adding peptone 1% with 7 days incubation time was detected in 5 pH variation (5, 5.5, 6, 6.5 and 7) while the effect of temperature were detected in 5 variations (30, 35, 40, 45, and 50oC). The research results showed that the time of incubation, the addition of peptone and ammonium nitrate affected significantly to enzyme production of rennet Mucor pusillus in â€œonggokâ€ medium. The highest production of the rennet enzyme products was in the addition of peptone 1% (12.53 RU/ml) with 7 days incubation time. On the treatment of temperature and pH, the optimum activity of rennet Mucor pusillus was in pH 5.5 (40.03 RU/ml) and the activity of rennet Mucor pusillus increased up to temperature of 50oC.